The Prevalence of Selected Potential Drug-Drug Interactions of Analgesic Drugs and Possible Methods of Preventing Them: Lessons Learned From the Analysis of the Real-World National Database of 38 Million Citizens of Poland - Kardas, Przemysław; Urbański, Filip; Lichwierowicz, Aneta; Chudzyńska, Ewa; Czech, Marcin; Makowska, Katarzyna; Kardas, Grzegorz (Frontiers in Pharmacology, 2021)
Introduction: Drug-drug interactions may lead to poor health outcomes, increased healthcare services utilization, and costs. Unfortunately, real-word data continuously prove high prevalence of potential DDIs (pDDIs) worldwide. Among identified drivers, ageing, multimorbidity and polypharmacy play very important role. With these factors being widespread, the need for implementation of strategies minimizing the burden of pDDIs becomes an urgency. This, however, requires better understanding of the prevalence of pDDIs and underlying causative factors. Aim of study: To assess the real-world prevalence of pDDIs and its characteristics in the general population of Poland, using analgesic drugs as a model, and to find out whether pDDIs are caused by prescribing coming from the very same prescribers. Methods: A retrospective analysis of the 2018 dispensation data of the National Health Fund - the only Polish public payer organization with nationwide coverage. We searched for selected pDDIs of non-steroid anti-inflammatory drugs (NSAIDs): with antihypertensives, NSAIDs (double use), oral glucocorticoids, oral anticoagulants, SSRIs, SNRIs, and antiplatelet drugs; as well as opiates with SSRIs, SNRIs, gabapentinoids, and benzodiazepines. A pDDI was deemed present if dispensation of both drugs standing in a possible conflict took place within the same calendar month. Results: Out of 38.4M citizens of Poland, 23.3M obtained prescribed drugs subject to reimbursement by NHF in 2018. In this cohort, we have identified 2,485,787 cases of analgesic drugs pDDIs, corresponding with 6.47% of Polish population. Out of these, the most prevalent pDDI was caused by “NSAIDs + antihypertensives” (1,583,575 cases, i.e. 4.12% of total Polish population), followed by “NSAIDs + NSAIDs” (538,640, 1.40%) and “NSAIDs + glucocorticoids” (213,504, 0.56%). The most persistent out of studied pDDIs was caused by “Opioids + Gabapentinoids” (2,19+/-1,90 month). On average, 76.63% of all cases of pDDIs were caused by prescribing coming from the very same prescribers. Conclusions: Using high-quality, nationwide data, we have found a high prevalence of analgesic drugs-related pDDIs in Poland. Over ¾ of the identified pDDIs came from the prescriptions issued by the same prescribers. The magnitude of the problem, illustrated with our findings of analgesic drugs pDDIs in Poland, deserves much more scientific and policymaker attention.